HUBUNGAN PELAKSANAAN NURSING ROUND DENGAN KINERJA PERAWAT DALAM PEMBERIAN ASUHAN KEPERAWATAN DI RSU ADVENT MEDAN - Hasibuan, Eva Kartika; Gulo, Adventy R. B; Saragih, Masri (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Nursing round is an activity whose purpose is to overcome patient nursing problems carried out by nurses and involve patients to discuss and carry out nursing care The implementation of nursing rounds can reduce errors in care and improve better performance results in the provision of nursing care The purpose of this study was to determine the relationship between the implementation of the nursing round and the performance of nurses in providing nursing care at Advent Medan General Hospital. The research design uses quantatid research with a cross-sectional approach. The population of this writing is all inpatient nurses at Advent Medan General Hospital which amounts to 115 nurses with a total sample of 53 taken using random sampling techniques. Data analysis using chi-square test. The results showed that the implementation of the majority of nursing rounds was good at 84.9%. The performance of nurses in the provision of nursing care was mostly high at 56.6%. There is a significant relationship between the implementation of the nursing round and the performance of nurses in providing nursing care at Advent Medan General Hospital with a p-value = 0.002 < 0.05. Therefore, it is better to carry out the continuous nursing round so that it can improve the ability of nurses in providing nursing care and as one of the aspects of monitoring evaluation in an effort to improve nurse performance.